2021
DOI: 10.1186/s40104-021-00647-2
|View full text |Cite
|
Sign up to set email alerts
|

Soya saponin improves egg-laying performance and immune function of laying hens

Abstract: Background Soya saponin (SS), an active compound in soybean meals, has been widely studied in the medical field. However, it was considered as an anti-nutritional factor in poultry diets. The objective of this experiment was to measure the effects of dietary SS using three dietary treatments on egg-laying performance and immune function of laying hens. Birds were fed a low soybean meal basal diet (CON), a low-SS diet (50 SS) containing 50 mg/kg SS, or a high-SS diet (500 SS) containing 500 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…Additionally, top 50 microbial genera were selected for calculation of Pearson's correlation coefficient, and then connections with a correlation coefficient greater than 0.6 and a significance level P < 0.05 were selected for network drawing (graphviz-2.38.0). It should be pointed out that the birds without antibiotics treated from our previous study ( Li et al., 2022b ) were bred together with the birds of the 2 treatment groups in this study, and their physical condition, diet and living environment are consistent.…”
Section: Methodsmentioning
confidence: 80%
See 3 more Smart Citations
“…Additionally, top 50 microbial genera were selected for calculation of Pearson's correlation coefficient, and then connections with a correlation coefficient greater than 0.6 and a significance level P < 0.05 were selected for network drawing (graphviz-2.38.0). It should be pointed out that the birds without antibiotics treated from our previous study ( Li et al., 2022b ) were bred together with the birds of the 2 treatment groups in this study, and their physical condition, diet and living environment are consistent.…”
Section: Methodsmentioning
confidence: 80%
“…To further study the influence of SS on the intestinal flora, the ileal flora data of laying hens with or without SS treated in the previous study ( Li et al., 2022b ) were used for co-occurrence network analysis. With SS supplementation, the dominant flora in the intestines was identified, and correlation analysis was carried out between this bacteria and related indexes of immunity and egg production performance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, several studies found that egg-laying rates in the late egg-laying period have a positive correlation with serum estrogen levels ( 1 , 45 ). Li et al ( 46 ) found that the egg production performance was improved by dietary supplements with soya saponin via increasing serum estrogen level. It is concluded that the addition of antioxidants to the diet can improve egg production to some extent by improving estrogen secretion.…”
Section: Discussionmentioning
confidence: 99%